(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
To see the factors that cause stunting in toddlers and warnings, as well as interventions that must be done to curb the stunting rate according to the needs and conditions of the Demak Regency community. This research uses a quantitative quantitative approach. The study population was the parents of children under five who were stunted in Demak Regency. Research data are in tabular form. The current national prevalence of stunting is 30.8%, in Central Java it is 31.22%, while in Demak it is 26.1%. According to WHO, the maximum limit for stunting patients is 20% of the total number of children under five. The direct causes of stunting are nutritional intake and infectious diseases. Indirect causes, namely victims of food at the household level, behavior or care for mothers and children, and health and environmental services. Environmental factors are the most important factor in the process of stunting compared to ethnic or genetic factors. Low public knowledge, poor hygiene, slum neighborhoods, lots of infectious diseases, contaminated or insufficient food, all in a poor environment. Maternal education and knowledge of maternal nutrition are factors related to the incidence of stunting in children under five. The factors causing stunting in Demak Regency are maternal education, family income, maternal knowledge about nutrition, offering exclusive breastfeeding, and fulfilling nutrition.